Accelerating drug development in pediatric cancer: a novel Phase I study design of venetoclax in relapsed/refractory malignancies. (29th March 2018) - Place, Andrew E; Goldsmith, Kelly; Bourquin, Jean-Pierre; Loh, Mignon L; Gore, Lia; Morgenstern, Daniel A; Sanzgiri, Yeshwant; Hoffman, David; Zhou, Ying; Ross, Jeremy A; Prine, Betty; Shebley, Mohamad; et al.
Venetoclax is a highly selective, potent BCL-2 inhibitor that is approved for some patients previously treated for chronic lymphocytic leukemia, and has shown promising activity in adult studies across several hematologic malignancies. Preclinical studies have demonstrated venetoclax activity in pediatric patient-derived xenograft models and cell lines; however, clinical studies in pediatric patients have yet to be conducted. The prognosis is poor for children with most relapsed/refractory malignancies, and limited treatment options result in unmet clinical need. Herein, we describe the rationale and design of the first study of venetoclax in pediatric patients with relapsed/refractory malignancies: a Phase I trial investigating the safety and pharmacokinetics of venetoclax monotherapy followed by the addition of chemotherapy (Trial registration: EudraCT 2017-000439-14; NCT03236857).